Application of Appropriate Technology to Revitalize Palm Sugar and Pepper Businesses in Lombo Village - Syahidah Syahidah; Makkarennu .; Muhammad Syahid; Asriana Abdullah; Andi Ahmad Rizaldy; Aulia Fatimah Khairunnisa (Faculty of Engineering UNHAS, 2026)
This community service program aims to increase the added value of palm sugar and pepper commodities in Lombo Village, Pitu Riase District, Sidenreng Rappang Regency, through social innovation downstreaming based on a sustainability approach. The activities were designed using the participatory rural appraisal method involving two partner farmer groups, the village government, and students. Interventions were implemented through socialization, hygienic production training, product diversification (palm sugar powder, liquid palm sugar, cube palm sugar, and pepper powder), assistance in adopting appropriate technologies (sap evaporator, dryer machine, grinder, and packaging machine), micro-enterprise management training, and digital marketing. Evaluation was carried out using pre–post tests, field observations, and semi-structured interviews to measure improvements in knowledge, skills, and business behavior. The results indicate increased community enthusiasm and participation, improved adoption of production technologies leading to higher process efficiency and product quality consistency. In addition, the program encouraged the formulation of a sustainability plan for farmer group institutions in managing village businesses based on local commodities.